Projek Sirib II establishment of Timpuyog Zambales, Inc.'s Online Educational Centers - Galace, Peter I.; Cruz, Edison (University of the Philippines Diliman, Quezon City Technology Management Center, 2009)
On August 2009, Timpuyog Zambales, Inc. (TZI), a non-government organization based in San Narciso, Zambales, will embark on a project to establish 15 Online Educational Centers (OECs) in the province of Zambales, Inc. Called Projek Sirib II, TZI's OECs will provide, for the first time, Internet access to the poorest communities of the province. Each OEC will be equipped with 50 to 75 desktop computers with broadband Internet connection plus wide-screen LCD TV monitors or LCD projectors, and DVD players for training and educational purposes. Considering that until today, there are hardly any computers in most public and even private elementary and high schools in Zambales, which means their students are hardly exposed to the use of computers, Internet or digital media, this project will be a big boost in upgrading the quality of education of students of Zambales. Not only will the students enjoy free use and training in basic computer programs, they will also enjoy broadband Internet service that will help them in their school research work and in communicating with other peoples of the world. In addition, the OECs will also provide them venues in further enriching what they learn from their teachers and books through educational video films, such as the 109-volume Sine Eskwela of ABS-CBN. But not only will the students benefit. Their teachers, school personnel, and even the public in general will be given a chance to also learn a basic computer lessons and given hands-on experiences on the use of computers. They will also be taught email, Internet browsing and other computer skills. In addition, the OECs will offer training programs like soap-making, bag-making and other livelihood training for parents and out-of-school-youth. These skills training will hopefully reduce unemployment problems in the poor communities, increase their income, and boost their productivities. The project proponent, Timpuyog Zambales, Inc. (TZI) [TIMPUYOG means "Unity" in Ilocano, a local dialect spoken in the central towns of Zambales province, Philippines], is a non-stock, non-profit, non-governmental organization (NGO) registered with the Securities and Exchange Commission, Philippines. It was organized in 2003 by a group of young professionals who banded together to contribute to the community's uplift by promoting ecologically sustainable economic development, dynamic community participation in local governance through continuing education and capacity-building, participatory program planning and implementation, social mobilization and policy advocacy. Timpuyog is not totally new to this kind of "digital divide" project. In 2006, it launched "Projek Sirib" (which roughly means, in Ilocano, Project Wisdom/Intellect) to provide computers and other electronic media equipment such as DVD's, projectors and CD players, to every barrio school in the municipality of San Narciso, Zambales for use by students and faculty. Projek Sirib's primary purpose was to build the capacity of community schools in educating elementary and high school students using a multimedia approach in keeping up with the requirements of a very fast-changing world. Projek Sirib was able to equip some Zambales schools with technologically advanced tools for learning : computers and digitized libraries in CDs; TV sets, DVD players and educational DVDs. By soliciting the support of Zambaleños now residing in foreign shores to contribute used computers, computer peripherals, and money for the purchase of brand new computers, TZI was able to raise half a million pesos and 50 computer systems that were eventually donated to at least 15 public and private schools in the town of San Narciso. But TZI realizes that more had to be done to really connect Zambales students to the digital world. The computers have to be linked to the worldwide web, teachers and students have to be taught on the proper use of computers, and they have to be trained as well on the use of computer software like Internet browsing software, MS Word, Excel, Email, etc. As conceived by TZI, an Online Educational Center will look like any ordinary classroom except that it will be equipped with 50 to 75 desktop personal computers, depending on the needs of the community where the OEC is located in. The computers will be wired to a network controlled by a server and computer will be provided with broadband internet connection. In addition, each OEC will also be equipped with wide-screen LCD TV monitor or LCD projectors, and a DVD player that will be used for training and educational purposes. These will be used for the basic computer courses and livelihood training programs that will also be offered free in all the OECs. In deciding which place will be chosen as an OEC site, Timpuyog will assign five persons who will evaluate each proposed site. Using a set of criteria, site evaluators will choose which site would be most feasible and appropriate to attain the objectives of Projek Sirib II. The criteria for the selection of an OEC site shall be as follows -- 1. Economic condition of the residents of the community (20 percent); 2. Suitability/Security of the Proposed School Site (20 percent); 3. Willingness of residents, barangay, and local officials to co-maintain the computers the OEC (15 percent); 4. Availability of reliable supply of electricity (10 percent); 5. Reasonable cost for the installation and monthly cost of broadband Internet service (20 percent); 6. Accessibility (15 percent). In choosing the best broadband Internet service provider for the OECs, PLDT's DSL service, Smart Bro, Digitel and Wit Global were considered. However, PLDT and its sister company, Smart, recently offered a broadband package for schools and other educational institutions at much lower rate of P3,000 to P5,000 a month, much lower than regular business rates. This is offered as part of the PLDT's efforts to contribute to the improvement of digital education in the Philippines. Thus, PLDT/Smart Bro. will be tapped for the broadband Internet service of the OECs. In deciding which place will be chosen as an OEC site, Timpuyog will assign five persons who will evaluate each proposed site. Using a set of criteria, site evaluators will choose which site would be most feasible and appropriate to attain the objectives of Projek Sirib II. The criteria for the selection of an OEC site shall be as follows -- 1. Economic condition of the residents of the community (20 percent); 2. Suitability / Security of the Proposed School Site (20 percent); 3. Willingness of residents, barangay and local officials to co-maintain the computers the OEC (15 percent); 4. Availability of reliable supply of electricity (10 percent); 5. Reasonable cost for the installation and monthly cost of broadband internet service (20 percent); 6. Accessibility (15 percent). In choosing the best broadband Internet service provider for the OECs, PLDT's DSL service, Smart Bro, Digitel and Wit Global were considered. However, PLDT and its sister company, Smart, recently offered a broadband package for schools and other educational institutions at much lower rate of P3,000 to P5,000 a month, much lower than regular business rates. This is offered as part of the PLDT's efforts to contribute to the improvement of digital education in the Philippines. Thus, PLDT/Smart Bro. will be tapped for the broadband Internet service of the OECs.
OECs will be open during office hours from 9:00 to 6:00 p.m., Mondays to Friday. Unless approved by the Project Manager, classes or training programs can be held on Saturdays between 9:00 a.m. and 6:00 p.m. This schedule will have to be strictly followed to save on electricity costs. Projek Sirib II will be managed by a Projek Sirib II Manager who will report primarily to the Timpuyog president and to the officers. The manager and his staff will be chosen by a majority vote of the officers of TZI. The OEC Project Manager will oversee and direct the operation of all OECs and will supervise all employees and volunteer teachers and other volunteer workers of the OECs. He/She will be assisted an Assistant Project Manager, a Treasurer, a Secretary and a Technician. There will also be Projek Sirib II OEC Site Supervisors who will oversee and direct the operations of the OEC in their areas of responsibility. They will make sure that classes are held on schedule, all computers are running and well-maintained, the OEC location is safe and secured, and rules regarding class schedules and use of computers are strictly followed. To ensure the smooth operation of all OECs, an OEC Site Supervisor will oversee the OEC in tandem with an OEC Advisory Group composed of-Principal of the school where OEC is located, Barangay Captain or Punong Barangay of the Barangay where the OEC is located, a local Municipal Official representative assigned by the Sangguniang Bayan of the municipality, and another non-government representative. The purpose of the Advisory Council is to ensure that the OEC gets the full support and backing of the local officials to ensure its smooth operation. To assist in the launch of Projek Sirib II, the officers of Timpuyog will be organizing four permanent committees. These are the -- Personnel, Purchasing, Finance and the OEC Site Preparation. Each committee will be headed by a chairperson and vice chairperson and will have three members each. The committee members will be drawn from regular members of TZI. To reduce risks and mitigate their effects should an unexpected event happen, a Risk Management Plan will be put in place by a Risk Management Team composed of the Project Manager, Asst. Project Manager, OEC Site Supervisors, OEC Site Asst. Supervisors, Computer Technicians, and members of the OEC Site Advisory Group. This team will meet at least once a month to review the status of all risk mitigation efforts, review the exposure assessments for any new risk items, and redefine the Projek Sirib's Top Ten Risk List. This project, will hopefully, be funded by Bill & Melissa Gates Foundation, Inc. under its annual Access to Learning Award. This award recognizes the innovative efforts of libraries or similar organizations outside the United States to connect people to information through free access to computers and the Internet. The recipient of the Access to Learning Award will receive US1 million dollars. Recent communications from the Foundation seem to indicate that there is a big chance of TZI getting the US1 million dollars grant. Projek Sirib II will run from August 2009 to August 2014 or for a period of 5 years, when the funding from the Bill & Melissa Gates Foundation would have been depleted. However, efforts shall be taken so that after that period, new funding could be obtained from local government officials or other funding agencies. Although funding from the Foundation usually is only up to a 5-year period, this also does not mean that we could no longer apply for an extension of Projek Sirib II, should the funder be satisfied with the results of the project. The start of the all major activities that will launch Projek Sirib II will start with the announcement of the Grant Award on the second week of August 2009, Anticipating that this project of TZI will be awarded with the US1 million dollars grant, Timpuyog will start forming the committees to launch Projek Sirib II on the last week of August. Major activities that will be undertaken include as soon as the grant is announced will be as follows : Preparation of OEC Sites for the whole month of October; Purchase of Computers and Other Materials for the period from last week of September to the whole month of October 2009; Installation of Broadband Internet Service on all OEC sites from last week of October to first 2 weeks of November; Hiring Process for OEC workers and teacher volunteers from September to November 2009; and Preparation of Computer Class Modules and Schedules from October to the whole month of November. The overall budget for the project is US1 million dollars or roughly equivalent to P48.5 million. The purchase of computers, peripherals, appliances, furniture, equipment and repair of OECs sites will cost a total Capital Expense of P16.448 million or approximately 34 percent of the total grant. Succeeding yearly budget is estimated at P7.4 to P8.04 million a year, for an estimated grand total of expenses in the next five years at P56.948 million, thus a shortfall in funds. Because of Interest Income, the shortfall is estimated at around P4 million. To make up for the shortfall, funds will be raised through donations from local government units and other non-government organizations in Zambales. TZI believes that with Projek Sirib II's success, government as well as other non-government organizations will share in the burden of maintaining the OECs. TZI officers have also pledged to start immediately fund-raising activities to meet the shortfall of funds in the fourth year of the project. As expected, the bulk of the Capital Expense will be for the purchase of 760 units of computers at P15,000 for a total amount of P11.4 million. Other big expenses are for the purchase of servers estimated at P800,000, LCD Projectors, P480,000 and Purchase of Operating Systems at P250,000. It should be noted that the budget for Operating Software has been reduced tremendously because the OEC will be buying in bulk and will surely get large discounts owing to the fact that the use of software will be for academic purposes. An item for contingency is also included in the Capital Expense, at half a million pesos. In conclusion, Projek Sirib II will be big help in improving the education of the Zambales elementary and high school students in poor communities in Zambales. Not only will the students enjoy free use and training in basic computer programs, they will also enjoy broadband Internet service that will help them in their school research work and in communicating with other peoples of the world. In addition, the OECs will also provide them venues in further enriching what they learn from their teachers and books through educational video films, such as the 109-volume Sine Eskwela of ABS-CBN. But not only will the students benefit. Their teachers, school personnel, and even the public in general will be given a chance to also learn basic computer lessons and given hands-on experiences on the use of computers. They will also be taught email, Internet browsing and other computer skills. In addition, the OECs will also have skills training programs like soap-making, bag-making, and other skills training for parents and out of school youth. These skills training will hopefully reduce unemployment problems in the poor communities and boost their productivities. Based on previous studies done here and abroad, the establishment of the OECs will not only be an effective way of bridging the digital divide in Zambales, but will also be empowering people from poor communities to be inspired to rise above poverty. By supporting this project and getting all sectors of the community to support it, we will be contributing a lot in eradicating poverty in poor communities in Zambales. In preparation for the award of the grant, the author prepared this paper to guide TZI in running Projek Sirib II. Thus this paper outlines the management, operation and administration of the Projek Sirib II and explains the different activities preparatory to the launching of the OECs.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Timpuyog Zambales, Inc; Online Educational Centers; Educational innovations; Continuing education centers; Projek Sirib II; Online educational centers